2015
DOI: 10.5296/ijl.v7i1.6750
|View full text |Cite
|
Sign up to set email alerts
|

EFL Teachers’ Code Switching in Turkish Secondary EFL Young Language Learner Classrooms

Abstract: This study investigated Turkish EFL Young Language Learner teachers' code switching (CS hereafter) from English to Turkish in their classroom discourse. The data were collected from two different secondary private institutions in Adana and Denizli. In accordance with this aim, three EFL teachers and their fifth-grade intermediate level classrooms were recorded for two class hours via video camera. The recordings were transcribed and explored to see whether these teachers resorted to CS or not, if so, what type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
4
8
0
1
Order By: Relevance
“…More specifically, 61% of teacher's code switching was classified as this type. This finding made the same with previous studies which had been conducted by Rezvani & Rasekh (2011), Rinda, (2014), and Yataganbaba & Yildirim (2015), where they also found that inter-sentential switching was used mostly by EFL teachers who taught EYL in their studies.…”
Section: Teacher's Inter-sentential Switchingsupporting
confidence: 90%
See 2 more Smart Citations
“…More specifically, 61% of teacher's code switching was classified as this type. This finding made the same with previous studies which had been conducted by Rezvani & Rasekh (2011), Rinda, (2014), and Yataganbaba & Yildirim (2015), where they also found that inter-sentential switching was used mostly by EFL teachers who taught EYL in their studies.…”
Section: Teacher's Inter-sentential Switchingsupporting
confidence: 90%
“…The use of Indonesian and Javanese was purposely done to ease two different kinds of addressees; the one who understood Indonesian better than Javanese and another party who understood Javanese better than Indonesian. Her strategy in using code switching to express her clear emotion in giving compliment and motivation made the same with the findings from Hoffmann (1991), Holmes (2001), Qian et al, (2009), Rezvani & Rasekh (2011), Rinda (2014), and Yataganbaba & Yildirim (2015).…”
Section: Examplesupporting
confidence: 66%
See 1 more Smart Citation
“…Several researchers have studied and investigated the functions, factors, characters and effects of code switching in wide ranges of linguistics domains. Yataganbaba, E., & Yildirim (2015) even claim that L1 use mainly results from lack of L2 proficiency in which the necessity of code switching is determined by the classroom condition because code switching may be considered as a useful strategy in classroom interaction, especially if the aim is to make meanings clear and to transfer the knowledge to students in an efficient way (Gabusi, 2007). The arguments given for mother tongue or L1 as medium of instruction in schools were more linked to the child and its needs, the individual and the local context, factors such as concept formation, cultural identity, and closer relation between school and home (Cantoni, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…They expressed their preference for using Turkish rather than having all-English lessons. In Yatağanbaba and Yıldırım's study, [30] code switching is found to be serving for the purposes of translation, metalanguage, asking equivalence, giving instruction and classroom management. Sali [20] found that mother tongue is used for a multiplicity of reasons.…”
Section: L1 In the L2 Classroommentioning
confidence: 99%